(untitled) (Literary Voice, 2023)
In recent times, robots have become increasingly human like both in their behaviour and appearance. Undoubtedly, such technological developments are essentially useful when it comes to preserving and improving the quality of life either in the fields of healthcare or education. But significant body of studies also demonstrates that humans frequently have a negative sense of eeriness, danger, and menace when they are around robots. This research paper will analyse the short story, "I, Robot" by Cory Doctorow through the prism of posthumanism and look at the problem of state or governmental monopolisation of information technology while acting as a deep state by subjugating the common masses through policing. The study further examines the negative and positive aspect of Isaac Asimov’s three laws of robots and the function that human consciousness plays in acceptance of robots that do not adhere to the three laws.